2017
DOI: 10.21511/imfi.14(1-1).2017.09
|View full text |Cite
|
Sign up to set email alerts
|

Financial market imbalance: reasons and peculiarities of occurrence in Ukraine

Abstract: Financial imbalance is the reason of a macroeconomic instability. This study aims at identifying the institutional causes of financial markets imbalance. The authors consider that financial intermediaries in Ukraine work in a speculative market segment carrying out high-risk transactions with the purpose of earning a huge profit. In fact, in Ukraine the role of these institutions in the investment process financing is insignificant. The authors show that soundness of banks along with the ease of access to loan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Slav'yuk et al emphasized that the main reason of financial market imbalances in Ukraine lies in the fact that financial intermediaries do not perform their functions of transforming the savings into real investments. Their operations have mainly speculative nature, and a high level of risk, and do not impact significantly the dynamics of GDP [Slav'yuk et al 2017].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Slav'yuk et al emphasized that the main reason of financial market imbalances in Ukraine lies in the fact that financial intermediaries do not perform their functions of transforming the savings into real investments. Their operations have mainly speculative nature, and a high level of risk, and do not impact significantly the dynamics of GDP [Slav'yuk et al 2017].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, many scholars, such as Gerschenkron (1962), Diamond (1984), Stiglitz (1985), Boyd and Prescott (1986), Bencivenga and Smith (1991), Bhide (1993), Stulz (2002), and many others, believed that a bank-centric financial system was superior to a market-centric one. According to this approach, banks perform the function of reducing information asymmetry and solve the problem of interim transaction costs and risks, and therefore have comparative advantages in terms of information collection, valuation of companies and ensuring relationships with companies (Gerschenkron, 1962;Opler, 1993;Rajan & Zingales, 2003, Čihák, Demirgüç-Kunt, Feyen, & Levine, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baur, Hong, and Lee [3] found that Bitcoin, which occupies the largest share of the cryptocurrency market, is mainly used as a speculative tool, and not as an alternative currency. The speculative nature of cryptocurrency would upset the balance in the financial market of Ukraine, the operations on which are aimed more at achieving high investment returns than ensuring GDP growth [4]. The results of empirical studies [3,5] find that cryptocurrency is uncorrelated with traditional asset classes such as stocks, bonds and commodities both in normal times and in periods of financial turmoil, which suggests their suitability for diversification of the investment portfolio with short horizons.…”
Section: Analysis Of Recent Researches and Publicationsmentioning
confidence: 99%